Two New Species of the Genus Aturus (Acari: Hydrachnidia) for the Turkish Fauna - Esen, Yunus; Erman, Orhan (Burdur Mehmet Akif Ersoy Üniversitesi, 2018)
It has been evaluated the species of the genus Aturus Kramer, 1875 collected from Bayburt, Ordu and Elazığ Provinces. Aturus rotundus Romijn, 1921 and Aturus villosus Motaş & Soarec, 1939 are new records for the Turkish fauna. Moreover, the morphological differences in the specimens Aturus scaber Kramer, 1875 has been evaluated. Further, a general assessment has been made on the species of the genus Aturus recorded from Turkey.

Bayburt, Ordu ve Elazığ illerinden toplanan Aturus Kramer, 1875 türlerinden Aturus rotundus Romijn, 1921 ve Aturus villosus Motaş & Soarec, 1939 Türkiye faunası için yeni kayıttır. Ayrıca Aturus scaber Kramer, 1875 örneklerindeki yapısal farklılıklar ile Türkiye’den kaydedilen Aturus türlerinin genel bir değerlendirmesi yapılmıştır.
Türkiye Faunası İçin Aturus Cinsinin (Acari: Hydrachnidia) İki Yeni Türü
Keywords: Engineering; Mühendislik